2020
DOI: 10.3390/ijerph17249320
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Adherence to Combinations of 24-h Movement Guidelines and Overweight and Obesity in Japanese Preschool Children

Abstract: The interactions between movement behaviors (physical activity, screen time, and sleep) affect the health of preschool children. Therefore, we examined the status of adherence to combinations of 24-hour movement guidelines (24-h MG) in Japanese preschool children and determined the associations between overweight/obesity and adherence to these 24-h MG. This cross-sectional study was conducted with 421 children aged 3–5 years (216 boys and 199 girls) living in the northeastern region of Japan. To evaluate the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
57
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 42 publications
7
57
0
3
Order By: Relevance
“…This suggests that compliance to movement behavior guidelines was associated with lower odds of overweight or obesity. This finding is consistent with another study which reported that Japanese preschool children who failed to meet movement behavior guidelines were more likely to experience overweight or obesity as compared to children who met all guidelines (OR: 1.139; 95% CI: 1.009–1.285) [ 18 ]. Preschoolers in China also showed lower odds for overweight and obesity when meeting screen time guidelines compared to those who did not meet screen time guidelines [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This suggests that compliance to movement behavior guidelines was associated with lower odds of overweight or obesity. This finding is consistent with another study which reported that Japanese preschool children who failed to meet movement behavior guidelines were more likely to experience overweight or obesity as compared to children who met all guidelines (OR: 1.139; 95% CI: 1.009–1.285) [ 18 ]. Preschoolers in China also showed lower odds for overweight and obesity when meeting screen time guidelines compared to those who did not meet screen time guidelines [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…The key finding indicates that up to 17% of preschoolers did not meet any of the physical activity, sedentary screen time and sleep time guidelines. This percentage was the highest as compared to studies conducted in Singapore (11.2%) [ 44 ], Australia (7.4%) [ 45 ], Japan (3.6%) [ 18 ], Canada (3%) [ 21 ], Belgium (2.9%) [ 46 ], China (2.7%) [ 19 ] and Sweden (0.5%) [ 20 ]. The present study found that only a very small percentage (6.5%) of preschoolers in Kuala Lumpur met all three guidelines.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…These associations were statistically signi cant over and above children's further health behaviors -physical activity and sleep, as well as income and other demographics. Our results substantiate the ndings from previous research that have shown a negative link between screen time and physical [50], social-emotional [51] and mental health [9] outcomes among preschool-aged children.…”
Section: Discussionsupporting
confidence: 91%